NON-VERBAL REPRESENTATION OF NARRATIVES IN THE LANGUAGE OF SCIENCE - Shelkovnikova , Z. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The considerations of scientific prestige, global competition among scientists, the speed and dynamics of modern life have led to the modifications in scientific discourse. Currently, scientists pay even more attention not only to the content of a message, but also to its form. The esthetic mode and narrativization have become the features of modern Anglo-American scientific discourse. The article deals with the narratives in the language of science through the prism of polycode nature of academic discourse. Various non-verbal research narratives are represented via book covers, pictures, images, graphs, diagrams and so on. The main characteristics of the research narrative, such as descriptive instruments, narrative intentionality, actionality, understandability, accessibility, creativity, logic, intrigue, esthetical mode were extensively illustrated with non-verbal narrative fragments found in scientific discourse. Narrative discourse stands out due to its eventfulness. We have paid special attention to the structural characteristics of the change of state, or condition, considering it as the main narrative feature. The action has been also considered in terms of singularity, fractality and intentionality. The action, together with the esthetical mode make the narrative scientific discourse stand out from the regular modes of research genres. The more narrative features we observe, the more evident is the narrative nature of a scientific discourse fragment. The language of science in the modern world is becoming more and more polycodal. Our research proves the polycode nature of narration in scientific discourse. _______________ References • Ilchenko O.M. Shelkovnikova Z.B. Naukoviy diskurs: shlyahi do (vzayemo)rozuminn’a / Lingvistika XXI stolittya: novi doslidgenna i perspektivi. – 2008. – N2. – s.131-139 • Kolegaeva I.M. Kognitsiya, semiosis, kommunikatsiya: o chem dumalos v minuvshiet 25 let / Zapiski z romano-germanskoyi filologiyi. – 2016. – Vip.1 – s.58-76 http://nbuv.gov.ua/UJRN/zrgf_2016_1_10 • Liotar J.F. (1979) Sostoyaniye moderna. – Sankt-Peterburg, 1998 • Lotman Y.M. Text i texti. – Lviv: Litopys, 1996 • Papusha I. Mignarodna naratologiya: problem definitsiyi [text] – Vip. 19.- 2007 – s.31-37 • Riker P. Vremya I raskaz. T.1. – M., 2000 • Tupa V.I. Chto takoye sobitiye 20.11.2015 Opennarratology www.opennar.com/single-post/2015/11/20что-такое-событие • Tupa V.I. Ocherk sovremennoy narratologiyi / Kritika I semiotika. – M., 2002. – Vip.5. www.nsu. ru/education/virtual • Shmid V. Narratologiya – : Yaziki slavyanskoy kulturi, 2008 • Shmid V. Proza kak poeziya – INAPRESS, 2001 • Whitehead A.N. Izbranniye raboti po filosofii. - M: Progress, 1990 • Yakhontova T.V. Lingvogenologiya suchasnoyi nauki (na materiali anglomovnih textiv): avtoref. d d-ra filol.nauk: spets. 10.02.04 – germanski movi; Kyiv. natz. un-t im. Tarasa Shevchenka. – K., 2014 • Fisher W. “The Narrative Paradigm: an Elaboration”. – Communication Monographs. 52 (4): 347-367, 1985 https://www.ibm.com/developerworks/rational/library/ • Hyland K. « Narrative, Identity and Academic Storytelling », ILCEA [Online], 31 2018, Online since 06 March 2018, connection on 06 March 2018. URL : http://journals.openedition.org/ilcea/4677 • Guaglione V. The Narratives: Keeping The Soul Alive. – Kindle Edition, 2013 • Guaglione V. The Narratives: From The Heart. – Kindle Edition, 2016 • Nixon R. 2015 Learning PHP, MySQL and JavaScript. – O’reilly, USA, 2015 • Pence L. Khara Turnbull Language Development From Theory – Pearson, 2016. • Sclar D. Learning PHP. – O’Reilly, USA, 2016